Wanoja Calakan: Langkah Menuju Digitalisasi Pemberdayaan Kader Perempuan - Solihah, Eneng; Wahyudin, Uyu; Saepudin, Asep (Jurnal Algoritma, 2025)
Women's empowerment is one of the important issues in global development. In Indonesia, the Wanoja Calakan organization strives to empower women through training and activities aimed at forming intelligent and agile female cadres. In facing the challenges of the digital age, it is important for these organizations to transform by utilizing technology. This research discusses the design of the Wanoja Calakan website which aims to improve efficiency in cadre registration, provide information about empowerment programs, and facilitate interaction between members and program managers. Agile methods are used in the design of this website to ensure adaptability to user needs and business processes that continue to evolve continuously. The website was tested using a usability test, resulting in a very good user acceptance score with an average score of 4.8 (96%) with a 95% confidence interval and a margin of error of 10%, using the Lemeshow formula. The result of this design is a user-friendly and responsive platform, which can be used to register cadres and access various information related to the program. In the future, this website is expected to be a more interactive means of empowering women in Indonesia